(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical and paraclinical characteristics of patients with benign prostatic adenoma undergoing monopolar transurethral resection of the prostate at Ha Tinh General Hospital. Materials and Methods: A retrospective descriptive study on 60 patients with benign prostatic hyperplasia (BPH) who underwent transurethral resection of the prostate (TURP) from January 2023 to December 2025 at Ha Tinh General Hospital. Results: The mean age was 76.25 ± 7.9 years. The most common presenting complaints were acute urinary retention (48.33%) and dysuria (43.33%). Most patients had severe symptoms (mean IPSS 21.53 ± 4.04) and impaired quality of life (mean QoL score 4.8 ± 0.85). The mean prostate volume was 67.28 ± 27.29 g. Conclusion: Patients with prostatic adenoma were predominantly elderly, presenting with severe lower urinary tract symptoms and markedly impaired quality of life. Prostate size was mainly in the moderate-to-large range, indicating suitability for transurethral resection of the prostate using monopolar electrosurgery.